2021
DOI: 10.1007/s11051-021-05379-y
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional Z-scheme NiO/Bi2WO6 heterostructures for enhancing visible-light photocatalytic activity

Abstract: Meanwhile, the photocatalytic mechanism of NiO/ Bi 2 WO 6 nanotubes has been discussed in detail. This work can act as a new technique to build p-n heterostructured photocatalysts, serving as a promising photocatalyst for the removal of TC-related antibiotics from the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…[ 18–20 ] Moreover, the low‐cost NiO compounded with band gap‐matched semiconductor materials, such as NiO/Ag 3 PO 4 , NiO/Bi 2 WO 6 and NiO/g‐C 3 N 4 , which can effectively improve the photocatalytic performance of heterojunction. [ 7,21,22 ] We found that NiO ( E CB = −0.09 eV, E VB = 2.61 eV) has a suitable band structure and matches well with BiO 2−x ( E CB = −0.46 eV, E VB = 1.26 eV). Therefore, it is possible to construct Z‐scheme heterojunction using NiO and BiO 2−x .…”
Section: Introductionmentioning
confidence: 70%
“…[ 18–20 ] Moreover, the low‐cost NiO compounded with band gap‐matched semiconductor materials, such as NiO/Ag 3 PO 4 , NiO/Bi 2 WO 6 and NiO/g‐C 3 N 4 , which can effectively improve the photocatalytic performance of heterojunction. [ 7,21,22 ] We found that NiO ( E CB = −0.09 eV, E VB = 2.61 eV) has a suitable band structure and matches well with BiO 2−x ( E CB = −0.46 eV, E VB = 1.26 eV). Therefore, it is possible to construct Z‐scheme heterojunction using NiO and BiO 2−x .…”
Section: Introductionmentioning
confidence: 70%
“…3(b)) nanoparticles shows bands at 268 and 717 nm that correspond to the intra-3d transition of Ni 2+ in the cubic structured NiO. 46 The UV-vis absorption spectrum of Fe 2 O 3 /NiO (Fig. 3(c)) is assigned to the characteristic absorption of pure Fe 2 O 3 and NiO.…”
Section: Resultsmentioning
confidence: 95%
“…In order to eliminate MB dye from effluent water, the cost‐effective, traditional, and influential approaches like adsorption, reverse osmosis, and dye coagulation are commonly used 14,15 . Nevertheless, complete extraction of MB dye is insufficient by these procedures 16,17 . Photocatalytic processes are the effective way to dissociate the organic contaminants into slighter harmful substance 18 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Nevertheless, complete extraction of MB dye is insufficient by these procedures. 16,17 Photocatalytic processes are the effective way to dissociate the organic contaminants into slighter harmful substance. 18 The photocatalytic efficiency of the semiconductors relies upon numerous variables like the bulk composition, phase, morphological structure, surface field, band alignment, and defect content.…”
mentioning
confidence: 99%